(3GdSeW GdMGhj ddege ef GdaJGhis - (3CHh RQYI GdMVQejs
(3ChdgG (B:s
(3GdMeO ddg GdPi HfYeJg JJe GdUGdMGJ hHYO adeG cGf ai aJGhi CUMGHfG ef GdeSGFd eG jcKQ hbhYgG , s
(3BNQgG (B:s
(3aGFOg dh CJJ CeJg HhdO aCfcQg , aTgO CHhg eY CLfHi HCfg CbQ HCfg hdOg bjd ai GdCUM EMJjGWkG ddfSH hGddg CYde GfJgi cJGH SeW GdMGhi s
(3HgG fXGe GdJYbjHIs
(3YdjgG JUMjMGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdecdG GdecJHg GdTYHjg s
Keywords: (3Gdabg GdTGaYjs